Báo cáo tiếp thu, giải trình ý kiến tham gia về dự án Luật Lực lượng tham gia bảo vệ an ninh, trật tự ở cơ sở - Bộ Công an (2021)
Toàn văn Báo cáo tiếp thu, giải trình ý kiến tham gia về dự án Luật Lực lượng tham gia bảo vệ an ninh, trật tự ở cơ sở.